The economics of religion anthropological approaches - Obadia, Lionel; Wood, Donald C. (Emerald, 2011)
The Economics of Religion explores the new paradigms of 'religious economics' and 'economies of religion' under the scope of transdisciplinary and international perspectives. It examines and appraises some of the recent theoretical developments and methodological innovations in religious and social sciences. This volume offers the chance to extend the analysis of religious behaviours by means of conceptual and methodological models of economics. It goes far beyond the classical 'economy and religion' debate, and suggests not only theoretical but also epistemological changes in the study of religion: individual rationality and rational choice, market theory, demand and supply theory, branding and commodification of religion, believers 'consumer' habits, churches competitive strategies, for example. Of course, these are not exempt from criticism, which this volume also addresses. These detailed and localized case-studies range from experimental to ethnographic methods, psychological to cultural aspects of believing and practising cults in the scope of economics of religion. Geographical areas covered include Nigeria, Bolivia, Italy, Mexico, France, Korea, Nepal and Tonga.
Keywords: Economics -- Religious aspects.; Religion -- Economic aspects.; elektronické knihy; electronic books